Climate Change Impacts on Natural Resources, Ecosystems and Agricultural Systems - Pande, Chaitanya B.; Moharir, Kanak N.; Singh, Sudhir Kumar; Pham, Quoc Bao.; Elbeltagi, Ahmed (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book on the climate change, natural resources, landscape and agricultural ecosystems describes the contributing challenges related to natural resources, soil erosion, irrigation planning, water, landscape, sustainable crop yield agriculture and biomass estimation. Natural resources and agricultural ecosystems include factors from nearby regions where landscape and agriculture practices (direct or indirect) interface with the water, vegetation, irrigation planning and ecology. Changes in climatic situations impact all the natural resources, ecology, and landscape of agricultural systems, which affects productivity. This book summarizes the various aspects of soil erosion, soil compaction, soil nutrients, aquifer and water with respect to vegetation, crops, pest and sustainable yields and management for the future. It also focuses on the use of precision techniques, remote sensing, GIS technologies, IOT and climate related technology for the sustainability of ecology, natural resources and agricultural areas, along with the capacity and flexibility of natural resources and agricultural societies under climate change. This book presents both theoretical and applied aspects and will help as a guide for future research. The contents will appeal to researchers, scientists, and NGOs working in climate change, environmental sciences, agriculture engineering, remote sensing, natural resources management, remote sensing, GIS, hydrologist, soil sciences, agricultural microbiology, plant pathology and agronomy.
Chapter 1. Impact of Climate Change on Livelihood Security and Biodiversity - Issues and Mitigation Strategies -- Chapter 2. Desertification Intensity Assessment within the Ukraine Ecosystems Under the Conditions of Climate Change on the basis of Remote Sensing Data -- Chapter 3. Climate Change effect on the urbanization: Intensified Rainfall and Flood Susceptibility in Sri Lanka. Chapter 4. Climate Change a strong threat to food security in India: With Special Reference to Gujarat -- Chapter 5. Livelihood vulnerability assessment and drought events in South Africa -- Chapter 6. Possible influence of urbanisation on rainfall in recent past -- Chapter 7. Influence of Climate Change on Crop Yield and Sustainable Agriculture -- Chapter 8. Hybrid Daily Streamflow Forecasting Based on Variational Mode Decomposition Random Vector Functional Link Network Based Ensemble Forecasting -- Chapter 9. Climate change and natural hazards in the Senegal river basin: dynamics of hydrological extremes in the Faleme river basin -- Chapter 10. Review of various impacts of climate change in South Asia Region, specifically Pakistan -- Chapter 11. Future Hydroclimatic Variability Projections Using Combined Statistical Downscaling Approach and Rainfall-Runoff Model: case of Sebaou River Basin (Northern Algeria) -- Chapter 12. Prediction of sugarcane yield in the semi-arid region based on the Sentinel-2 data using vegetation's indices and mathematical modelling -- Chapter 13. Effect of urbanism on Land Surface Temperature (LST) in a river basin and an urban agglomeration -- Chapter 14. Estimation of Land Surface Temperature and Urban Heat Island by using Google Earth Engine and remote sensing data -- Chapter 15. Study on irrigated and non-irrigated lands in Ukraine under climate change based on remote sensing data -- Chapter 16. Hybrid Kernel Extreme Learning Machine Based Empirical Wavelet Transform for Water Quality Prediction using Only River Flow as Predictor -- Chapter 17. Assessment of Climate Change Impact on Land Use-Land cover using Geospatial Technology -- Chapter 18. Impacts of climate-induced events on the season-based agricultural cropping pattern and crop production in the Southwestern coastal region of Bangladesh -- Chapter 19. Towards Smart agriculture for climate change adaptation -- Chapter 20. Flood Impact and Damage Assessment based on the Sentitnel-1 SAR data using Google Earth Engine -- Chapter 21. Application of Hyperspectral remote sensing role in Precision Farming and Sustainable Agriculture under climate change: A Review -- Chapter 22. Tools and solutions for watershed management and planning under climate change -- Chapter 23. Isotopic proxy to identify climate change during the Anthropocene -- Chapter 24. Estimation of Land surface temperature for Rahuri taluka, Ahmednagar District (MS, India) using Remote Sensing data and Algorithm -- Chapter 25. Analytical Hierarchy Process (AHP) based on the spatial assessment of an endangered alpine medicinal herb Aconitum heterophyllum in the Western Himalayan environment -- Chapter 26. Land use and cover variations and problems associated with coastal climate in a part of southern Tamil Nadu, India using Remote sensing and GIS approach -- Chapter 27. Classification of vegetation types in the mountainous terrain using random forest machine learning technique -- Chapter 28. Water conservation structure as an unconventional method for improving sustainable use of irrigation water for Soybean Crop under rainfed climate condition -- Chapter 29. Study of Image segmentation and classification methods for climate data analysis.
Keywords: Climatology; Power resources; Environmental economics; Earth sciences; Water; Hydrology; Geography; Climate Sciences; Resource and Environmental Economics; Earth Sciences; Water; Geography